Shape shift - Hesselberth, Joyce (Christy Ottaviano Books, Henry Holt and Company, 2016)
"Round, curvy, pointy, or straight-shapes are all around us. With illustrations that highlight shapes in all their forms, this book reinforces the identification of circles, squares, crescents, diamonds, triangles, rectangles, trapezoids, and ovals while encouraging kids to pair shapes together to make new forms"--